What You Wear Can Change Your Life - Trinny Woodall & Susannah Constantine
Continuing their entertaining guide to fashion, the authors of What Not to Wear offer straightforward advice on fashion and explain how to develop a personal style suited for one's body type and personality, with helpful tips on choosing colors and accessories, the art of clothing storage, special advice for pregnant women, make-up, stylish underwear, and more.